Performance of in silico tools for the evaluation of p16INK4a (CDKN2A) variants in CAGI. Issue 9 (16th May 2017) - Carraro, Marco; Minervini, Giovanni; Giollo, Manuel; Bromberg, Yana; Capriotti, Emidio; Casadio, Rita; Dunbrack, Roland; Elefanti, Lisa; Fariselli, Pietro; Ferrari, Carlo; Gough, Julian; Katsonis, Panagiotis; et al.
Abstract : The Critical Assessment of Genome Interpretation (CAGI) experiment is aimed to define the state of art of genotype‐phenotype interpretation. Here, we present the assessment of the CAGI p16INK4a challenge. Participants were asked to predict the effect on cellular proliferation of ten variants for the p16INK4a tumor suppressor, a kinase inhibitor coded by the CDKN2A gene. Twenty‐two pathogenicity predictors were validated in terms of accuracy and reliability. Different assessment measures were combined in an overall ranking to provide robust results. Abstract: Correct phenotypic interpretation of variants of unknown significance for cancer‐associated genes is a diagnostic challenge as genetic screenings gain in popularity in the next‐generation sequencing era. The Critical Assessment of Genome Interpretation (CAGI) experiment aims to test and define the state of the art of genotype–phenotype interpretation. Here, we present the assessment of the CAGI p16INK4a challenge. Participants were asked to predict the effect on cellular proliferation of 10 variants for the p16INK4a tumor suppressor, a cyclin‐dependent kinase inhibitor encoded by the CDKN2A gene. Twenty‐two pathogenicity predictors were assessed with a variety of accuracy measures for reliability in a medical context. Different assessment measures were combined in an overall ranking to provide more robust results. The R scripts used for assessment are publicly available from a GitHub repository for future use in similar assessment exercises. Despite a limited test‐set size, our findings show a variety of results, with some methods performing significantly better. Methods combining different strategies frequently outperform simpler approaches. The best predictor, Yang&Zhou lab, uses a machine learning method combining an empirical energy function measuring protein stability with an evolutionary conservation term. The p16INK4a challenge highlights how subtle structural effects can neutralize otherwise deleterious variants.